2013
DOI: 10.3109/00207454.2012.758123
|View full text |Cite
|
Sign up to set email alerts
|

Expression of β-catenin and E- and N-cadherin in human brainstem gliomas and clinicopathological correlations

Abstract: Brainstem gliomas are usually associated with serious dysfunction and poor prognosis especially for diffuse intrinsic brainstem gliomas; however, the reasons are still unclear. Some clinical studies have suggested that the invasive ability may be different among brainstem gliomas, and the dysfunction of β-catenin and E- and N-cadherin appears to be connected with tumor invasion and progression. In this study, the expression of β-catenin and E- and N-cadherin was detected in 40 brainstem glioma samples using im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Although E-cadherin suppression is observed in the brain cancer tissues, the functions of E-cadherin in the tumor cells remain to be verified as another cadherin member, and N-cadherin seems to plays a more significant role in brain cancer aggressiveness. Low E-cadherin expression is found in most of the glioblastoma tissues and is associated with the differentiation status of the glioblastoma [56, 57]. In comparison with the tumor tissues, E-cadherin expression is rare in the glioblastoma cell lines [58, 59].…”
Section: Brain Cancermentioning
confidence: 99%
“…Although E-cadherin suppression is observed in the brain cancer tissues, the functions of E-cadherin in the tumor cells remain to be verified as another cadherin member, and N-cadherin seems to plays a more significant role in brain cancer aggressiveness. Low E-cadherin expression is found in most of the glioblastoma tissues and is associated with the differentiation status of the glioblastoma [56, 57]. In comparison with the tumor tissues, E-cadherin expression is rare in the glioblastoma cell lines [58, 59].…”
Section: Brain Cancermentioning
confidence: 99%
“…A previous study on brainstem glioma showed that higher expression of CDH2 predicts the progression of malignant tumors and tends to predict a shorter survival time of patients [ 31 ]. Other studies also indicated CDH2 may be functionally correlated with tumorigenesis in glioma cells and involved in mediating glioma cell migration [ 32 - 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cadherin 2 (CDH2), which encodes the N-cadherin protein, is also a marker of EMT. An increasing amount of evidence has suggested that CDH2 has a close association with the WHO grade of glioma (10). By contrast, a previous study demonstrated that GBMs express lower CDH2 levels than low-grade gliomas (11).…”
Section: Introductionmentioning
confidence: 89%